An integrative framework for coopetition-based scenarios - Budler, Marko (Economic and business review, 2024)
The interplay of cooperation and competition (“coopetition”) in supply chains is well studied. However, little is known about the established and evolving scenarios that exist among supply-chain actors in the presence of coopetition. The paper draws on the resource-based view and game-theoretic reasoning to develop an integrative framework with two aims. First, to classify coopetition-based scenarios with varying levels of complementarity and lastingness and to enhance the analysis of the scenarios. Second, as theoretically argued and demonstrated with a focus group discussion, the framework is developed to assist supply chain actors in strategically managing coopetition - by identifying a particular scenario and adjusting their resources and capability structuring, bundling, and leveraging accordingly.
Keywords: competition; konkurenca; management; preskrbovalne verige; risk; supply chain; tveganje